A Framework for Understanding the Strategies of Openness of the Intelligence Services. Issue 3 (2nd September 2021) - Díaz-Fernández, Antonio M.; Arcos, Rubén
ABSTRACT: The relationship of the intelligence services with openness has been elusive and erratic, changing at the path of the scandals that shaked politics and public opinion. At different rhythms and marked by their national contexts, different intelligence services have embarked over the last two decades in different initiatives to promote societal awareness and a better understanding among society on the intelligence function. In this paper, a theoretical framework is proposed for understanding those openness strategies implemented by the intelligence agencies. The paper discusses two potential approaches to openness with a spectrum of mixed approaches in-between them. The first consists of generating and maintaining a (good) image/reputation and, the second is to legitimize its existence and its role within the State.